Leakage fault detection in Electro-Hydraulic Servo Systems using a nonlinear representation learning approach. (February 2018) - Sharifi, Siavash; Tivay, Ali; Rezaei, S. Mehdi; Zareinejad, Mohammad; Mollaei-Dariani, Bijan
Abstract: Electro-Hydraulic Servo Systems (EHSS) are employed as actuators to track the desired trajectory and exert force in heavy-duty industrial applications. The EHSS is often prone to problems such as leakage and actuator seal damage during the course of its utilization. These faults which cannot be directly detected from current sensor values, can eventually result in complications and degrade control performance. The goal of this research is to use representation learning concepts to detect these faults with decreased complexity. The objective is to find a nonlinear mapping to transform raw data into another space in which classification becomes easier. The data are driven from the hydraulic supply pressure signal. To find the mapping, a custom-built optimization algorithm is proposed along with a suitable cost function to carry out the search for the new representation. The performance of the resulting transformation is tested in an experimental setting to show the merits of the proposed method. Highlights: A novel approach to detect leakage fault in the Electro-Hydraulic Servo Systems. A feature extraction method is used in order to reduce dimensionality. A nonlinear mapping to transform raw data into another space with decreased complexity. Find the mapping using an iterative custom-built optimization algorithm. Effectiveness is verified via simulation and experimental data.